2018
DOI: 10.1021/jacs.8b09070
|View full text |Cite
|
Sign up to set email alerts
|

Exploiting Intermolecular Interactions between Alkyl-Functionalized Redox-Active Molecule Pairs to Enhance Interfacial Electron Transfer

Abstract: The strategies to enhance electron transfer rates between redox-active, light-harvesting molecules attached to semiconductor surfaces and redox mediators in solution by modifying molecular structure are not fully investigated yet. Therefore, the design of molecules with controlled electron transfer rates remains a challenge. The aims of this work are to quantify the effect of long alkyl chain substitution on the electron transfer from cobalt(II/III) tris(2,2′-bipyridine) to organic molecules containing carbazo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
50
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 21 publications
(55 citation statements)
references
References 31 publications
1
50
0
Order By: Relevance
“…Attractive intermolecular interactions between electron donor and acceptor have been a recently emerging factor to enhance interfacial electron transfer. In 2018, we reported a way to enhance electron transfer kinetics when a densely packed dye layer is present [33] . Unexpectedly, when both a dye (MK2) and a redox mediator had long alkyl chains, electron transfer was enhanced due to alkyl‐alkyl intermolecular interactions (see Figure 17).…”
Section: Electronic Coupling (Hda) Effect Of Redox‐active Molecules O...mentioning
confidence: 98%
See 2 more Smart Citations
“…Attractive intermolecular interactions between electron donor and acceptor have been a recently emerging factor to enhance interfacial electron transfer. In 2018, we reported a way to enhance electron transfer kinetics when a densely packed dye layer is present [33] . Unexpectedly, when both a dye (MK2) and a redox mediator had long alkyl chains, electron transfer was enhanced due to alkyl‐alkyl intermolecular interactions (see Figure 17).…”
Section: Electronic Coupling (Hda) Effect Of Redox‐active Molecules O...mentioning
confidence: 98%
“…In 2018, we reported recombination rates in DSCs using a series of alkyl‐substituted Co complexes paired with dye molecules decorated with hexyl chains [33] . The recombination rates were slowed down by a factor of two using nonyl‐substituted Co complexes as compared to that of the methyl‐substituted Co complex at the same Δ G ° and electron density.…”
Section: Electronic Coupling (Hda) Effect Of Redox‐active Molecules O...mentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, to address these issues, several alternatives have been used. On the one hand, functional groups that are used as anchors have been introduced further from the active side by using long alkyl chains as spacers in the linkers [75,83,84]. This approach causes fewer electronic changes in the active side of WOCs as well as minimizes direct interactions with the (photo)electrode surface, preserving their catalytic activity and minimizing electron-hole recombination, respectively.…”
Section: Covalent Immobilizationmentioning
confidence: 99%
“…It is well‐known that the introduction of electron withdrawing and donating groups has a significant effect on their redox potentials and catalytic activity , , . To address the former issue, Wang et al suggested the utilization of anchoring groups with long alkyl chains , , . They found that long‐chain anchors are more effective than shorter ones to preserve catalytic activity of molecular electrocatalysts.…”
Section: Immobilization Of Molecular Electrocatalysts By Covalent mentioning
confidence: 99%